Avaliação de diferentes marcadores de dano oxidativo, genotoxicidade e inflamação em trabalhadores expostos a solventes no município de Santa Maria, RS - Silva, Lilian Marquezini da (2015)
The organic solvents, also known as volatile organic compounds (VOCs) or volatile hydrocarbons, are widely used in a variety of industrial processes and consumer products. Gas station attendants (G.S.A.), as well as painters, are potentially exposed to these hydrocarbons such as benzene, toluene and xylene. Thus, the main of this work was to verify laboratory findings in workers exposed to these solvents. Blood and urine samples were collected to verify the biological indicators of exposure to these solvents, as well as inflammatory, genotoxicity and oxidative damage markers. The results showed an increase in malondialdehyde (MDA) levels in the G.S.A. group, while painters group presented an increase in nitric oxide (NO) levels. Among the genotoxicity markers, an increase in 8-hydroxydeoxyguanosine (8-OHdG) levels in G.S.A. and painters groups was observed and, in this last group, the increase was even greater. The G.S.A. group presented significant DNA damage compared to the control group, which was demonstrated by the comet assay. Among the inflammatory markers, interleukin-1 (IL-1), interleukin-6 (IL-6), tumor necrosis factor alpha (TNF-α) and interferon gamma (IFN-γ), the levels were increased in both groups compared with the control group, and painters showed higher levels of IFN-γ compared to the G.S.A. group. Interleukin-10 (IL-10) levels were significantly reduced in both groups of workers exposed, when compared to the unexposed group. Moreover, a significant increase was observed in alanine aminotransferase (ALT) activity in painters. Hematological parameters were changed in painters, since there was a reduction in platelet count and increase in mean corpuscular hemoglobin (MCH). The biological indicators of exposure to these solvents, trans, trans muconic acid (t, t mA) for benzene, hippuric acid (HA) for toluene and metilhipuric acid (mHA) for xylene, were not modified in G.S.A. and painters compared to control group. Despite these indicators remained within the maximum permissible values, significant changes were observed in other markers, revealing mainly changes in the specific markers for inflammation and genotoxicity.